2020
DOI: 10.3390/foods9101375
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Vanilla Oleoresin (V. planifolia Andrews) by Complex Coacervation and Spray Drying: Physicochemical and Microstructural Characterization

Abstract: Vanilla is one of the most popular species in the world. Its main compound, vanillin, is responsible for its characteristic aroma and flavor and its antioxidant and biological properties. Vanillin is very unstable in the presence of oxygen, light, and humidity, which complicates its use and preservation. Therefore, to solve this problem, this study aimed to develop vanilla oleoresin microcapsules. Vanilla oleoresin was obtained with supercritical carbon dioxide and microencapsulated by complex coacervation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Chen et al (2020) reported a particle size range of 370–1191 nm for complex coacervation of zein‐chitosan treated by cold plasma technology (Chen et al, 2020). Hernández‐Fernández et al (2020) studied the encapsulation of vanilla oleoresin using chitosan–gum Arabic complex coacervates, and the particle size ranged from 85.86 to 1936.38 nm, with polydispersity index values in the range of 0.27–0.88 (Hernández‐Fernández et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2020) reported a particle size range of 370–1191 nm for complex coacervation of zein‐chitosan treated by cold plasma technology (Chen et al, 2020). Hernández‐Fernández et al (2020) studied the encapsulation of vanilla oleoresin using chitosan–gum Arabic complex coacervates, and the particle size ranged from 85.86 to 1936.38 nm, with polydispersity index values in the range of 0.27–0.88 (Hernández‐Fernández et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Hernández-Fernández et al ( 2020) studied the encapsulation of vanilla oleoresin using chitosan-gum Arabic complex coacervates, and the particle size ranged from 85.86 to 1936.38 nm, with polydispersity index values in the range of 0.27-0.88 (Hernández-Fernández et al, 2020).…”
Section: Size Of Chitosan/persian Gum Complexmentioning
confidence: 99%
“…Encapsulation is a term used for processes in which the active/core material is totally enveloped in a coating or wall material, and thus it is separated and protected from the surrounding environment. Different encapsulation techniques were used to preserve, store, and incorporate VA in various food matrices (Hernández‐Fernández et al., 2020). Among these techniques, flavor emulsion is considered as one of the most suitable methods to encapsulate flavors in cloudy fruit juices.…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulation of flavorings has also been aimed among the published investigations of this issue. Hernández-Fernández et al [ 12 ] have developed vanilla oleoresin microcapsules, evaluating the conditions of complex coacervation (percentage of gum Arabic and chitosan, and pH) and the influence of spray-drying. According to the findings of this work, it is possible to microencapsulate vanilla oleoresin extracted through complex coacervation and spray-drying, which allowed the protection of the volatile compounds to be increased and a higher stability.…”
mentioning
confidence: 99%
“…The optimal conditions found were 0.34% and 1.7% of gum Arabic and chitosan, respectively, at pH 5.29. Li et al [ 12 ] have investigated the effect of maltodextrine with different dextrose equivalent values (6, 7 and 12) to encapsulate ethyl acetate. In this study, the use of maltodextrine with a high dextrose equivalent, and whey protein as wall materials provided the best protection for flavor substances during storage, and increased their release during dissolution.…”
mentioning
confidence: 99%